Osthole Improves Spatial Memory Deficits in Rats via Hippocampal α1-Adrenergic and D1/D2 Receptors. (26th February 2013) - Lin, Li-Wei; Kuo, Yueh-Hsiung; Hseu, You Cheng; Tsai, Chia-Wen; Hsieh, Ming-Tsuen; Chen, Shiu Ching; Wu, Chi-Rei
Abstract : The present study evaluated the effect of osthole, an active ingredient isolated from Cnidium monnieri L. Cusson, on spatial memory deficits caused by central neurotoxins using the Morris water maze in rats. The involvement of catecholaminergic receptors on the memory-enhancing effect of osthole in rat hippocampus was further investigated by intrahippocampal injection of catecholaminergic receptor antagonists. Intracisternal injection of osthole (10 μ g/brain) improved the spatial performance and working memory impairments caused by the catecholaminergic neurotoxin 6-hydroxydopamine. No significant differences in swimming speeds were observed among sham, neurotoxin-induced, and osthole-treated groups. Intracisternal osthole injection also attenuated the spatial performance and working memory impairments caused by the α 1 receptor antagonist phenoxybenzamine, the D1 receptor antagonist SCH 23390, and the D2 receptor antagonist sulpiride. Therefore, we demonstrated that the effect of osthole on improving spatial memory deficits may be related to the activation of hippocampal α 1 and D1 /D2 receptors.